Weathered Pages: Artists’ Books and Ecocritical Materialities - Barbara Garrie (Interfaces)
This article explores the contemporary artist’s book as a site of ecocritical enquiry. More specifically, it takes a deep dive into three works that offer meditations on human entanglements with weather: Roni Horn’s Weather Reports You (2007), Jeremy Deller’s Speak to the Earth and It Will Tell You (2007-17), and Marina Kampka’s Weather Forecast (2014). These books are significant in how they reveal the complex and interrelated material and narrative agencies at play in storying the environmental systems we call “weather”. Central to this article are the ways in which these exchanges are enabled and amplified by the book form. The pages of each book are surfaces for rich narrative expression, enlivened by their own bookish materiality and the complex networks of production and circulation within which they are situated, and wherein they perform as a kind of threshold or porous interface between human and more-than-human worlds.